Literatura latinoamericana mundial - Guerrero, Gustavo; Locane, Jorge L.; Loy, Benjamin; Müller, Gesine (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo, 2020)
From the perspective of Latin American Studies, this volume offers a critical contribution to the current debate on world literature. It is structured around three conceptual blocks: gatekeepers, as the dispositives and actors mediating the international circulation of literature translation, as an unavoidable but always problematic mechanism and local literatures, as modes of writing that remain intrinsically tied to their contexts.